Mapping the susceptible areas from violence against women and children - Handayani, Arri; Widodo, Suwarno; Maulia, Desi (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2022)
This research aimed to (1) arrange the violence vulnerability indicator area and (2) map the potential areas from violence against children and women. This mix-method research used a sequential exploratory design. The researchers took the qualitative data by interviewing 32 Integrated Service Center officers in Semarang during a FGD. The quantitative research involved 648 people from 16 districts in Semarang taken randomly. The data collecting instruments included an interview guidance, gender-role orientation scale, and parenting scale. The obtained secondary data were from the Central Statistical Bureau in Semarang, the Marital Age data from the Ministry of Religion Semarang, and the data on violence against children and women from the Woman and Child Protection Agency, DP3A, Semarang. The results from the FGD were (1) poverty, incomplete family, low educational access, reported violence rate, patrilineal culture, number of children, and early marital as the factors of violence prevalence, and (2) The indicators of vulnerable areas from violence included poverty, population density, slum, unemployment, drug abuse, socio-economic gap, early marriage, patrilineal culture, and ignorant families. Then, in the second data phase, the researchers found 27.9% of traditional gender role orientation and 72.1% of non-traditional gender role orientation. For parenting patterns, a percentage of 6.5% population applied permissive parenting patterns, 14.8% applied authoritarian parenting patterns, and 78.7% applied democratic parenting patterns. The results found the potential areas with the highest violence were Pedurungan and Eastern Semarang districts. Then, the Southern Semarang and Tugu districts were the areas with the lowest violence prevalence rates. Keywords: Violence against women and children, mapping regions